(untitled) (Development Service Industry Management, 2025)
The study presented in this article focuses on the impact of the Russian-Ukrainian war on the intensification of tourism activity in eastern Slovakia, in particular in the Presov and Košice regions. The war significantly changed the socio-economic processes in Central and Eastern Europe, which also affected the tourism industry in these countries. Eastern Slovakia, which is located in proximity to Ukraine, has become one of the main destinations where tourist flows have been reoriented. The humanitarian and geopolitical challenges associated with the war have stimulated the growth of domestic tourism, as well as an increase in the number of tourists from Ukraine and other regions. The article pays special attention to the study of the Agreement between Ukraine and Slovakia on cooperation in the field of tourism, which plays an important role in the development of bilateral contacts and promotes the integration of tourist flows between the countries. Based on the analysis of statistics for 2022-2023, a significant increase in the number of tourists visiting Slovakia was noted, in particular due to increased security and accessibility for refugees from Ukraine. The Prešov and Košice regions, as strategic regions in terms of cross-border cooperation, have experienced the greatest changes in tourist flows. The study shows that in 2023, the number of tourists in Slovakia increased significantly, reflecting not only the stability of the situation in the country, but also the intensification of domestic and cross-border tourism. The number of tourists in the Prešov and Košice regions also increased due to the growing demand for active and passive tourism, including outdoor recreation and visits to cultural attractions. An important factor was also the improvement of infrastructure for temporary accommodation for refugees. The results of the study show that the Russian-Ukrainian war has had a positive and negative impact on tourism activity in Slovakia. On the one hand, the war contributed to the growth of domestic tourism, but on the other hand, it worsened the international image of the region. Nevertheless, the introduction of new tourism programs and strategies can help to further develop tourism in these regions.